Therapeutic Potential of Dioscorea Extract (DA-9801) in Comparison with Alpha Lipoic Acid on the Peripheral Nerves in Experimental Diabetes - Heung Yong Jin; Sun Hee Kim; Hea Min Yu; Hong Sun Baek; Tae Sun Park (Journal of Diabetes Research)
DA-9801, a mixture of extracts from Dioscorea japonica Thunb. and Dioscorea nipponica Makino, was reported to have neurotrophic activity. Therefore, we investigated the therapeutic potential of DA-9801, in comparison with alpha lipoic acid (ALA), for peripheral nerves preservation in experimental diabetes. Experimental animals were divided into 4 groups, and each group was designated according to the type of treatment administered as follows: normal, DM, DM+DA-9801, and DM+ALA. After 16 weeks, response thresholds to tactile and thermal stimuli were higher in DM+DA-9801 group than in nontreated DM group. This degree of increase in DM+DA-9801 group indicates more therapeutic potency of DA-9801 than ALA. Western blot analysis showed more significant increase in NGF and decrease in TNF-α and IL-6 in DM+DA-9801 group than in DM or DM+ALA groups (P<0.05). IENF density was reduced less significantly in the DM+DA-9801 group than in other DM groups (7.61 ± 0.32, 4.2 ± 0.26, and 6.5 ± 0.30 in DM+DA-9801, DM, and DM+ALA, resp., P<0.05). Mean myelinated axonal area in the sciatic nerves was significantly greater in DM+DA-9801 group than in other DM groups (69.2 ± 5.76, 54.0 ± 6.32, and 63.1 ± 5.41 in DM+DA-9801, DM, and DM+ALA, resp., P<0.05). Results of this study demonstrated potential therapeutic applications of DA-9801 for the treatment of diabetic peripheral neuropathy.